MANAJEMEN STRATEGIK SEKOLAH BERBASIS BOARDING SCHOOL DALAM MENINGKATKAN KUALITAS MUTU PENDIDIKAN - Misraini, Misraini; Marsithah, Iis; Mulyadi, Said (Research and Development Journal of Education, 2024)
This study aims to analyze the strategic management of boarding school-based education in improving the quality of education at junior high schools in Central Aceh Regency. The research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The subjects include school principals, teachers, and school committees at junior high schools implementing the boarding school system in Central Aceh Regency. The findings reveal that during the planning stage, schools involved various stakeholders, including committees and the community, and utilized SWOT analysis to design strategic programs tailored to the schools' needs. In the implementation stage, the integration of academic and character-building programs, such as Quran memorization, Arabic language learning, and extracurricular activities, effectively enhanced students' holistic competencies. Meanwhile, in the evaluation stage, principal-led supervision emphasizing transparency and accountability positively impacted teacher performance and the quality of educational programs. The study concludes that boarding school-based strategic management can improve education quality by integrating religious and locally relevant approaches suited to the community context. This model can be adopted by other schools to sustainably enhance educational quality.